AKULTURASI ISLAM DENGAN BUDAYA LOKAL - Agus Sriyanto (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2007)
Nowadays, especially in Java, it is difficult to flnd pure and original actualization of Islam. This condition is influenced by the Javanese and Hinduism traditions which had been tightly held by the society before the arrival of Islam. These traditions really influence the spread of Islam. Da’wa cultural approaches which were applied by Da ’i greatly influences the existence of Islam at this time. Without dismissing or changing the social culture, Islamic values are inserted to them and people can easily accept Islam. However, there is a negative effect of this model, which causes the occurrence of sincretism between a religion, in this case, Islam and local culture.